Some problems of Alasdair Macintyre’s ‘emotivism thesis’ - Olszynka, Szymon (Hybris, 2016)
In this article Alasdair MacIntyre’s thesis concerning emotivist use of moral utterances in contemporary liberal societies is analysed. One tries to show that it needs further clarification since at least three elements of MacIntyre’s argument seem to pose certain problems; these are: ‘discussion halt’ as the source of emotivism, comprehensive doctrines as premises of respective arguments in liberal debates and the problem of incommensurability. These three problematic elements are discussed and interrelations between them are adumbrated.